Nurturing lifestyles: the determinants of health prevention behaviors in Portugal - Novais, Andreia Raquel Ferreira (2024)
The Portuguese National Health Surveys were used to answer the question “What are the determinants of health prevention behaviors?”. The health behaviors considered were exercise, healthy diet, no smoking and prudent alcohol consumption. The variables of interest included demographic information, socio-economic factors and healthcare related variables. A maximum likelihood estimation was performed using a multivariate probit model. The results point to the importance of secondary education, while also highlighting the importance of income for a healthy diet. Differences were found between the NUTS II regions, which, alongside the influence of General Practitioners, should be considered when developing healthcare policies